A new genus and species of Paralimnini leafhoppers from Israel (Hemiptera: Cicadellidae: Deltocephalinae) - Sinaiko, Guy; Dietrich, Christopher H. (Zootaxa, 2020)
A new genus and species of the leafhopper tribe Paralimnini are described from Israel, viz., Paraphysifer Sinaiko & Dietrich gen. n. with P. wilsoni Sinaiko & Dietrich sp.n. as type species.